Combustion-derived BaNiO3 nanoparticles as a potential bifunctional electrocatalyst for overall water splitting. (1st May 2023) - Junita, J.; Jayalakshmi, D.; Rodney, John D.
Abstract: Electrochemical water electrolyser though an assuring solution for clean hydrogen production, the sluggish kinetics and high cost of existing precious metal electrocatalyst remains a barrier to its effective utilization. Herein, solution combustion route derived perovskite type barium nickelate (BaNiO3 ) nanoparticles were developed and studied for their bifunctional electrocatalytic properties towards overall water splitting. The unannealed BaNiO3 nanoparticles exhibited the highest OER and HER activity with overpotentials 253 mV and 427 mV respectively to attain 10 mAcm −2 in 1.0 M KOH. Using unannealed BaNiO3 as a bifunctional electrocatalyst in a two-electrode alkaline electrolyser, the cell was able to achieve the benchmark current density at a low cell voltage of 1.82 V. Impressively the setup's electrocatalytic performance improved 4.9% after continuous overall water splitting for 24 h at 30 mAcm −2 . Therefore, BaNiO3 nanoparticles can be a low-cost and efficient alternative for noble metal electrocatalysts for clean H2 production. Graphical abstract: Image 1 Highlights: BaNiO3 nanoparticles were prepared by economical & rapid solution combustion method. The BU/BU cell presents non-deteriorative operation for 24 h. 2.7% & 12.8% of OER & HER activity gain was observed post 12 h stability test.